The Effectiveness of Convergence, Adaptive Ease, and Saccade Movements on the Reading Ability of Primary School Students with Dyslexia: A Randomized Clinical Trial - Hanieh Falahati; Amanullah Soltani; Mitra Kamiabi; Hamdollah Manzari-Tavakoli (Vesnu Publications, 2021)
Introduction: The ability to read and understand is one of the most vital skills in the modern world today. Due to the fact that many people have reading problems, the need for early and correct diagnosis and effective treatment is felt. The aim of the present study was to determine the effectiveness of convergence, adaptive ease, and saccade movements on reading ability in primary school students with dyslexia in Rafsanjan, Iran.Materials and Methods: This study was a randomized clinical trial in which 45 subjects were selected from all second grade students with dyslexia in Rafsanjan in the academic year 2019-2020 by purposive sampling method and randomly divided into experimental and control groups. The intervention was performed in 15 sessions of 30 minutes. The control group, with the agreement of the child and the parents, did not receive any parallel treatment process during the study. In the experimental and control groups, the Analysis of Persian Reading Ability (APRA) test was used. Multivariate analysis of covariance (MANCOVA) was used to analyze the data.Results: Convergence, adaptive ease, and saccade movements had a significant effect on improving reading ability in children with dyslexia (P < 0.010).Conclusion: Convergence, adaptive ease, and saccade movements may effectively improve reading accuracy and comprehension ability in children with dyslexia.